DA’WAH, RELIGIOUS ACTIVISM AND DIGITAL ARENA: THE EXPERIENCES OF STUDENT ACTIVIST’S IN UNIVERSITAS NEGERI MALANG, INDONESIA - Titis Thoriquttyas; Nurul Ahsin; M Nabil Khasbulloh (The Pontianak State Institute of Islamic Studies, 2023)
The dynamic of da’wah among students have special characteristics in packaging da’wah content, selection of da'i and contextual trends in it. In addition, student figures of da’wah activists are representations of urban Muslims who are closely related to religious symbols, especially in the digital arena. Da’wah and religious activism in the digital arena, especially within the scope of urban youth, are the core topics of this research. This study took a sample on the Instagram posts of UKM BDM al Hikmah Universitas Negeri Malang by focusing on the da’wah narratives used. Through Bourdieu's habitus theory, Weber's theory of religious authority and visual semiotics, virtual da’wah narratives and the existence of da'i chosen by BDM al Hikmah, UM and the selection of da’wah content are two important problem formulations in this research. The findings of this study provide an overview of the position of preachers in the digital space having at least three capitals, namely social, charisma and rational. Meanwhile, in the visual semiotics review, the choice of language and discussion of da’wah that is carried out is more in accordance with the contexts and contemporary problems faced by listeners, there has been a dynamic negotiation process between the da’i and the listener